FACILITATING PLAY DIVERSITY IN PRIMARY SCHOOL OUTDOOR SPACES - Elma Mahfuzhoh; Syam Rachma Marcillia (Journal of Architecture & Environment, 2026)
Playing outdoors at school provides children with opportunities to understand and engage with their spatial surroundings, shaping their cognitive awareness of the school environment. In Indonesian public elementary schools, outdoor areas are expected to support both educational and recreational functions; however, their actual use during recess remains underexplored. This study investigated how children used outdoor school spaces for play during recess at SDN Gondolayu, Yogyakarta, using place-centered behavior mapping complemented by a children’s perception survey. From 172 observed activity groups, non-play activities constituted the largest proportion of recess use, followed by restorative play, indicating limited engagement in active play. Boys used outdoor spaces more frequently than girls and showed different play tendencies, while age differences between lower (Grades 1–3) and upper (Grades 4–6) groups were minor. Spatial analysis revealed that children predominantly occupied corridors, edges, and other in-between areas that were flexible and loosely programmed rather than formal courts. Survey responses further indicated higher enjoyment in socially interactive and expressive forms of play. The predominance of non-play activities across locations suggests that several parts of the school environment were unable to support diverse play opportunities. In the absence of dedicated playgrounds and varied environmental features, children used transitional and semi-enclosed spaces that offered enclosure, proximity to peers, and opportunities for engagement. These settings enabled both refuge and social interaction within the same spatial field, indicating that children’s play experiences were shaped by the combined spatial qualities of school environments rather than by isolated features or equipment alone. These findings highlight how the spatial characteristics of school environments shape children’s play behavior and experiences. Understanding children’s interactions with informal and transitional outdoor settings can inform schoolyard design strategies that support more diverse and engaging play opportunities in primary school settings.